Examining the relationship between social determinants of health with daily tobacco use, binge-drinking, and daily cannabis use - Zoe Lindenfeld; Ellen T. Kurtzman (PLoS ONE, 2026)
Introduction There is growing recognition that social determinants of health (SDOH) shape health behaviors in powerful ways. Given that risky substance use remains a persistent public health problem, the relationship between SDOH and substance use merits investigation. The objective of this study is to examine the relationship between various social determinants of health (SDOH) with binge drinking, daily tobacco use, and daily cannabis consumption. Methods Using the most recent Behavioral Risk Factor Surveillance System data (2022–2023) we conducted two sets of logistic regression models. The first examined relationships between our three outcomes and 13 separate SDOH measures. The second assessed a categorical, composite SDOH measure and our outcomes. Results Frequent stress was associated with significantly higher odds of each outcome (binge drinking: AOR 1.27, 95% CI: 1.13–1.42; tobacco: AOR 1.16, 95% CI: 1.02–1.32; cannabis: AOR 1.43, 95% CI: 1.22–1.68). Having a recent medical checkup was associated with lower odds (binge drinking: AOR 0.84, 95% CI: 0.75–0.95; tobacco: AOR 0.77, 95% CI: 0.67–0.88; cannabis: AOR 0.82, 95% CI: 0.71–0.96). Higher cumulative SDOH-needs were associated with significantly higher odds. For cannabis: 1–3 needs: AOR 1.54, 95% CI: 1.27–1.87; 4–6 needs: AOR 3.35, 95% CI: 2.64–4.25; 7–13 needs: AOR 4.61, 95% CI: 3.32–6.41. Similar patterns were observed for other outcomes. Conclusions Findings should inform interventions to reduce substance use by directly addressing SDOH associated with increased risk and by supporting the co-location of social and health services to better meet individuals’ complex needs.